Giftedness and ADHD: A systematic literature review - Soares Coutinho-Souto, Waleska Karinne (2022)
The purpose of this study was to examine the scientific production of empirical articles regarding twice exceptionality – giftedness/ADHD – through a systematic review. The search was carried out in the Portal de Periódicos Capes, SciELO, and PePSIC databases, considering the publications between 2011 and 2021. The terms giftedness, high abilities, ADHD, twice exceptionality, and their counterparts in Portuguese were used as descriptors. We selected 27 articles based on pre-established inclusion criteria. Six categories of studies were identified: socio-emotional factors, interpersonal relationships, identification, inattention and hyperactivity, intelligence quotient, and educational support practices. The conclusion was that by having their individual needs met and school community support, gifted students with ADHD can academically succeed, have a positive self-concept and good interpersonal relationships.